PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR NEGERI 93 PEKANBARU - Tengku Yusmaniar; Otang Kurniaman; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
The results of this research is that the application of cooperative learning modelNumbered Head Together (NHT) can improve student learning outcomes IPA offifth grade in SD N 93 Pekanbaru, it can be seen from: (1) an increase in theactivities of teachers at each meeting, where the meeting I 58.33% percentage ofteacher activity and the second meeting increased to 72.91%, an increase of14.58%. At the third meeting increased to 79.17%, an increase of 6.26%, and at ameeting of IV increased to 95.83%, an increase of 16.66%. (2) Increased activityof students at each meeting, in which the first meeting of the percentage of studentactivity and 43.70% in the second meeting increased to 58.33%, an increase of14.63%. At the third meeting increased to 75.00%, an increase of 16.67%, and thefourth meeting increased to 95.83%, an increase of 20.38%. (3) Improved studentlearning outcomes from baseline score to the second cycle, which on the basis ofthe average score of student learning outcomes 61,50, the first cycle increased to69.17 with an increase of 12.47%. In the second cycle of the average studentlearning outcomes at 83.67, with an increase of 36.05%. (4) Improving studentlearning outcomes in the classical style on the base score is 43.33%, in the firstcycle increased to 60.00%, an increase of 16.67% and in the second cycleincreased to 90.00%, an increase of 30 , 00%.Keywords: Cooperative Learning, the result of science study